The Redistributive Effects of the Tax System in West Germany, Sweden, and the United States: A Comparative Tax Incidence Study - Christoph Rosenberg (Luxembourg Income Study (LIS), 1989)
This paper contains a comparative international tax incidence study, investigating taxation and its effects on income redistribution in West Germany, Sweden, and the United States.
Keywords: 330